Histology, embryology, cytology: textbook - Данилов, Р. К. гистология 19440507 Ревхат Константинович (Textbook, 2022)
This textbook sets out the latest ideas regarding cell structure, cytophysiology, development, structure and age-related changes in all human tissues and organs. It reviews the sequential stages and critical periods of human development. Along with fundamental issues, much attention is given to the applied medical aspects of histology. Moreover, it refl ects issues of reactivity and tissue regeneration caused by extreme environmental factors including fi rearm, which have not lost their relevance today due to local confl icts and the spread of weapons among the population. The most complex organized histological structures and biological processes are illustrated by drawings, light-optical and electronic micrographs and diagrams. The present texbook is intended for students of medical universities, military academies and foreign military personnel studying the specialties 31.05.01 General Medicine, 31.05.02 Pediatrics, 31.05.03 Dentistry, 32.05.01 Medical and Preventive Care, as well as teachers, graduate students, and clinical laboratory scientists.